REPRESENTASI PESAN DAKWAH MELALUI VIDEO ANIMASI DI AKUN TIKTOK @KAKEKTIKTOK-ANIMATORAMATIR - Anggreini Siregar, Rizka Syahputri; -, Suyanto (Universitas Teuku Umar, 2025)
Da'wah is the heart of religion, because religious life is very dependent on dynamic movements and da'wah activities that run continuously without end. The tiktok account @KakekTikTok-AnimatorAmatir is one of the user who uses social media as a means of preaching. This study aims to analyze how the representation of the meaning of denotation, connotation and myth in the message of da'wah adab dressed as Muslim women and the wise use of women in Tiktok social media on the Tiktok account @KakekTikTok-AnimatorAmatir.This study uses a qualitative research method with a Roland Barthes semiotic analysis approach, namely denotation, connotation, myth with 14 data analysis units. Data were collected through observation, documentation, and literature studies, with theoretical triangulation for data validity.The results of this study show: First, the meaning of denotation is presented through elements that are displayed directly in the video, namely audio and visual, such as the appearance of medium shots, close-ups, full shots, long shots, the use of emotional melodic audio, bright lighting and electronic equipment. Many scenes are shown in a quiet and tense setting. Second, the meaning of the connotation is presented through the appearance, intonation of the voice and the meaning behind the message conveyed about women's manners, responsibility, and continue to follow Allah's commands. Thus forming a myth in the form of messages that are believed by the public visually and verbally.